An Analysis Relative to the Complex of Dreams Formation (Global Journal of Human-Social Science, 2021)
Dreams are defined as a sequence of images, thoughts, and emotions passing through one's mind during the activity of sleep. Hence, it is comprehensively related to sleep as it is produced much during the cycle of sleep. Therefore, to analyze more about dreams, it is essential to know about sleep. The definition of sleep states that it is a state of rest in which one's eyes are closed, the body becomes inactive, and the mind does think nothing; it is also defined as a rest afforded by a suspension of voluntary bodily functions and the natural suspension complete or partial of consciousness. There is a contradiction in the definition between the words sleep and dream. The dream is defined as thoughts passing through one's mind during the activity of sleep, and sleep is defined as the mind does think nothing. Let us discuss the contention in detail.
Keywords: dreams; thoughts; mind; and sleep